Numerical study of heat transfer and fluid flow in a symmetric wavy microchannel heat sink reinforced by slanted secondary channels - Qifeng Zhu; Xianyao Liu; Jingwei Zeng; He Zhao; Wenqiang He; Haoxin Deng; Guoyan Chen (Case Studies in Thermal Engineering)
To improve the thermal and hydraulic performance of symmetric wavy microchannel heat sinks, a novel design has been devised with slanted secondary channels from trough to crest based on its pressure distribution characteristics. These channels connect regions of adverse pressure gradient in any two neighboring channels to form a novel microchannel heat sink (SW-TC). Employing three-dimensional numerical simulations, a comparative analysis was performed on the flow and heat transfer characteristics among the SW-TC, the symmetric wavy microchannel with wave crest-to-crest secondary flow channels (SW-CC), and the symmetric wavy microchannel with wave trough-to-trough secondary channels (SW-TT). The results indicate that the design of slanted secondary channels significantly improves fluid mixing across channels, suppresses boundary layer development, and consequently enhances the heat transfer efficiency and overall performance of the SW-TC. The SW-TC achieves its peak relative Nusselt number and overall performance factor at 1.835 and 1.843, respectively. Furthermore, the SW-TC exhibits excellent temperature uniformity across the heating wall, and its temperature increase along the flow direction is a mere 8.3 K at Re = 200. It also presents the lowest entropy generation number among all designs, reaching 0.56 at Re = 100.